Changing Professional Practice, Training Balkan History Educators to Become Agents of Change. Issue 1 (1st December 2001) - Van Der Leeuw-Roord, Joke
Abstract : Essential is the long term role of history education in providing a back cloth to the development of plural democracies. Nowhere is this more starkly illustrated than in societies moving rapidly from one political system to another predicated upon diametrically opposed principles. The Balkans provide an object lesson for the importance of history education: here we see a heady brief of nationalism, socialism and tribalism being decanted into new democratic bottles. The long-term hope of such societies lies in changing the values, beliefs and attitudes of its citizenry. One element in this equation is the educational system, within which history education plays as big a role as it did under communism.